Nurse to Nurse: Nursing Management - Knodel, Linda J. (McGraw-Hill, 2020)
Real-world solutions to nurse management issues Unlike other books on the subject, Nurse to Nurse: Nursing Management goes beyond theory and academic discussion to provide real-world solutions to the management problems nurse managers face today. Written by a Chief Nursing Officer with two decades of hands-on experience, this portable, and user-friendly text includes real-life case studies and algorithms to assist the decision-making process...